Too Busy to Be Fair? The Effect of Workload and Rewards on Managers’ Justice Rule Adherence - Sherf, Elad N.; Venkataramani, Vijaya; Gajendran, Ravi S. (Academy of Management Journal, 2019)
Why do managers act unfairly even when they recognize the significant organizational benefits of treating employees fairly? Prior research has explained this puzzling phenomenon predominantly through an “actor-centric” perspective, proposing that managers’ just behavior is an outcome of their own individual differences. This paper shifts the locus of theorizing away from managers to their organizational context by arguing that managers’ adherence to principles of justice is often influenced by two key contextual features—workload and rewards. Drawing on the multiple-task pursuit framework, we propose that under high workloads, just treatment of employees often competes with other managerial tasks. We further argue that organizations implicitly and explicitly signal to managers that acting justly is not as important as their other technical tasks. Hence, managers who face high workloads (i.e., high amounts of work and time pressures) tend to prioritize other technical responsibilities at the expense of acting justly, unless explicitly rewarded otherwise. We find support for our theorizing across three studies (an experience sampling study, a field study, and an experiment). We discuss the implications of our theory and findings for future research on managerial fairness and offer novel practical implications for organizations attempting to ensure employee fair treatment.